Edukasi tentang Penyakit Myastenia Gravis pada Pengunjung Poliklinik Neurologi Rumah Sakit Universitas Mataram - Herpan Syafii Harahap; Ilsa Hunaifi; Muhammad Ghalvan Sahidu; Yanna Indrayana; Susilawati Ni Nyoman Ayu; Diayanti Tenti Lestari; Fitriannisa Faradina Zubaidi; Nurhidayati Nurhidayati; Legis Ocktaviana Saputri (Universitas Mataram, 2022)
Myasthenia gravis is one of the most common autoimmune diseases at the neuromuscular junction. Although this disease is rare, the incidence of this disease is believed to have increased in the last seven decades. This community service activity aims to provide education to the public regarding myasthenia gravis. This community service activity was carried out in the form of counseling at the Neurology Polyclinic of UNRAM Hospital on Friday, January 20 2023. All participants were asked to take part in all counseling activities which consisted of pre-test activities, delivery of material on the topic of myasthenia gravis, and post-test. The enthusiasm of the participants in this activity was presented in the form of photo documentation. Statistical analysis using paired t-test was carried out to analyze the difference between the pre-test and post-test mean values ​​and the results were considered significant if a p value <0.05 was obtained. As many as 23 participants who attended the Neurology Polyclinic at UNRAM Hospital enthusiastically participated in the whole series of activities. The average participant post-test score was significantly higher than the pre-test means score (p = 0.025). This activity was able to increase the participants' knowledge about myasthenia gravis.